Integrasi Seni Kuno dan Tantangan Enkripsi Modern melalui Kajian Ulang Teknik Kriptanalisis Al-Kindi - Anandari, Anatansyah Ayomi (UIN Sunan Gunung Djati Bandung, 2023)
This study aims to review the cryptanalysis techniques introduced by Al-Kindi, an ancient cryptographic figure, by relating them to the modern encryption challenges faced today. The method used involves an analysis of the literature on Al-Kindi's works which are relevant in cryptanalysis, such as “Risalah al-Mu'atabarah